Clinical Influences in the Multidisciplinary Management of Small Renal Masses at a Tertiary Referral Center. Issue 6 (November 2016) - Lallas, Costas D.; Scotland, Kymora; Zhang, Michael; Schaeffer, Daisey; Calvaresi, Anne E.; Gomella, Leonard; Brown, Daniel; Shaw, Colette; Trabulsi, Edouard J.
Abstract : Introduction: : We designed a multidisciplinary Small Renal Mass Center to help patients decide among treatment options and individualize therapy for small renal masses. In this model physicians and support staff from multiple specialties work as a team to evaluate and devise a treatment plan for patients at the same organized visit. Methods: : We retrospectively reviewed the records of 263 patients seen from 2009 to 2014. Monitored patient characteristics included age, Charlson comorbidity index, body mass index, nephrometry score, tumor size and estimated glomerular filtration rate. Univariate and multivariate analyses were performed to identify patient characteristics associated with each treatment choice. Results: : Of the cohort 88 patients elected active surveillance, 64 underwent ablation and 111 were treated with surgery, including partial and radical nephrectomy in 74 and 37, respectively. There were significant associations between treatment modality and age, Charlson comorbidity index, tumor size and estimated glomerular filtration rate. Mean patient age at presentation was 61.1 years. Patients with a high Charlson comorbidity index score (greater than 5) or a decreased estimated glomerular filtration rate (less than 60 ml/minute/1.73 m 2 ) were more likely to undergo active surveillance (41.6% and 35%) and ablative therapy (29.6% and 34%) vs partial nephrectomy (10.6% and 9%, respectively, each p <0.001). On multivariable analysis age, tumor size and estimated glomerular filtration rate remained significantly associated with modality after adjustment for all other factors (each p <0.001). Conclusions: : The Small Renal Mass Center enables patients to assess the various treatment modalities for a small renal mass in a single setting. By providing simultaneous access to the various specialists it provides an invaluable opportunity for informed patient decision making.